Purification of oil wastewater - Semenova, Olena; Bublienko, Natalia; Smirnova, Elizabeth; Shylofost, Tatiana (My University, 2012)
The given article discusses the problem of treatment of oil wastewater. It is known that the problem of oil wastewater treatment is topical nowadays, because as a result of various technical and technological processes the formed oil wastewater is not utilized properly. The article provides the information of pollution of oil waste¬water which is produced by the food enterprise, and also the ways of its purification. The objective of research is the intensification of the process of biochemical treat¬ment. Scientific novelty of the research lies in biosorbtion of oil gas-liquid counter-current mode and oxidation in an airtank-clarifier.

Для очищення нафтовмісних стічних вод запропонована схема блоку біохімічсекого окислення, яка включає в себе біосорбції і окислення з використанням взвещених шарів активного мулу. Проведено порівняння основних показників процесу очищення нафтовмісних стічних вод в одноступенчатом аеротенку змішувачі і в блоці біохімічного окислення.
Keywords: oil wastewater; pinotank; biochemical purification; нафтовмісна стічна вода; біохімічна очистка; біосорбції; пенотенк; кафедра екології та екоменеджменту; кафедра іноземних мов професійного спрямування